Metode Iterasi Orde Dua Trapesium untuk Menyelesaikan Persamaan Nonlinear - Faliha, Hammi; Subhan, Muhammad (Journal of Mathematics UNP, 2023)
Mathematical problems in determining the roots of nonlinear equations can be solved analytically and numerically. However, very complex nonlinear equations are difficult to solve analytically, so numerical methods are used. Trapezoid Second Order Iteration Method is a method that emerge because of the shortcomings of the Newton Raphson Method and The Secant Method. The purpose of this study is to examine the process of forming the formula for the Trapezoid Second Order Iteration Method, develop an algorithm and find its convergence. This type of research is basic research. The result of numerical simulation tests on several function whose approach point are at two peaks show that The Trapezoidal Second Order Iteration Method is faster than Newton Raphson Method.